(untitled) (Journal of Plant Disease Sciences, 2018)
The roving survey was conducted during Kharif season 2017-18 in Vidarbha region of Maharashtra in order to know the per cent disease incidence of Alternaria leaf spot of soybean and results revealed that maximum mean per cent disease incidence (41.66%) was observed in Walgoan village of Amravati district followed by in Mozari (40.19%) Tahsil Tiwsa district Amravati. Whereas minimum percent disease incidence (12.50%) was noticed in village Tuljapur Taluka Seloo district Wardha followed by Jambhrun Parande village in Washim district (13.93%). Total 440 bits of infected leaf sample of soybean Alternaria leaf spot subjecting for isolation, the main pathogen isolated was Alternaria alternata (85.92%) followed by Alternaria tenuissima (3.85%). This indicated that Alternaria alternata was the major pathogen species associated with soybean in Vidarbha region.